Continuing education for the public secondary school library personnel in the Division of Quezon City a follow-up study - Quinto, Mae Lyn P.; Faderon, Rosalie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1998)
The study determined the perceived continuing education needs of secondary public school library personnel in the Division of Schools of Quezon City. Specifically, it aimed to identify the library personnel's educational background, constraints involved in attending continuing education programs, the continuing education programs in the last fourteen years; and lastly, to find out if the recommendations of Ms. Elizabeth Bautista were implemented.
The population was composed of public secondary high school librarians found in different districts of Quezon City. A total of 37 schools including five annexes found in the four districts of Quezon City were surveyed. The study used the interview, observation and questionnaire as instruments and the library personnel were selected through a universal method. The questionnaires were personally handed to forty-two out of forty-nine secondary school library personnel. Three of the respondents were on maternity leave or sick leave. Two of the respondents did not wish to be included in the survey and four of the respondents were not present when the survey was conducted.
Findings of the study revealed that: 1) Most of the library personnel of the public secondary schools in the Division of Quezon City are teachers. Majority of them are degree holders of Bachelor of Secondary Education. 2) The perceived continuing education needs of these library personnel librarianship were in the areas of cataloging, management, reference, selection and acquisition, and information technology. 3) The library personnel were not properly informed about the continuing education programs in librarianship. 4) For the past fourteen years, the Division of Schools in Quezon City sponsored continuing education programs.
The minor findings of the study were: 1) Majority of the school library personnel are females; there are only two males. 2) Thirty-seven schools in the public secondary schools have library personnel. 3) Sixty-seven percent (67) of the personnel had attended continuing education programs during the last 14 years. But most of them are not in librarianship. 4) Majority of the library personnel who wanted to attend the continuing education programs did so to "update their knowledge in school librarianship", "to comply with the requirements of RA 6966", and "to compare notes with colleagues". 5) Majority of the respondents are degree holders of Bachelor of Secondary Education; five of the respondents were teacher-librarians; and eleven of them were school librarians. 7) Eleven of the respondents are newly assigned to the library, i.e., they came in only in 1997). 8) Seventy-nine percent (79 percent) of the total numbers of respondents have teaching load. Only 21 percent of the library personnel are full time librarians. 9)Forty-three percent (43 percent ) are members of library associations such as Philippine Librarians Association, Inc. (PLAI), Philippine Association of Academic and Research Libraries (PAARL), Quezon City Public Librarians Association, (QCPLA), MPSLA and University of the Philippines Library Science Alumnae Association (UPLSAA). 10) Majority of the libraries have very scarce collection. Most of the librarians seek help from the Rotary Club, ASEAN and other institutions and organizations that usually donate books. However, some of the books donated were already obsolete. 11) Majority of the librarians are English teachers. Most of the libraries are under the supervision of the English department. The Quezon City Science High School and Ramon Magsaysay High School are the two schools whose libraries are under the school administration. They are independent of the English department. 12) Majority of the librarians are concerned about the budget that the library should have.
Based on the findings, the following recommendations are drawn: 1) Findings and recommendations made from this and E. Bautista's studies should be disseminated to the head of the Division of Schools of Quezon City and to the Philippine Association of School Librarians (PASL) in order to pave the way for their implementation as well as conduct a deeper study into the plight of libraries and librarians in the public secondary schools. 2) The Division of Schools of Quezon City should create or work towards the creation of position for full-time librarians and supervising librarians to ensure the proper and continuing management of library resources and services in these libraries. 3) The Division of Schools of Quezon City should allot adequate funds not only for the allowances of library personnel in attending continuing education programs but also for the regular library budget of the school libraries. 4) The PAARL, PASL and other library organizations should offer reasonable fees for the continuing education programs that they will conduct in the future. They should be aware that not all librarians can afford to pay high registration fees. 5) The principal should give more attention to the needs of the library personnel and to its library collection. 6) The library should be directly under the principal of the school. 7) School authorities should assign school librarians with definite job descriptions and should offer reasonable salaries. 8) Follow-up studies should be done at least after every five years to see if the situation or the condition of the library personnel and the library have improved.
Vita.
Computer print out.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Library employees -- Philippines -- Quezon City; Library education (Continuing education) -- Philippines -- Quezon City